Urinalysis and Clinical Correlations in Patients with P. vivax or P. falciparum Malaria from Colombia (2017)
ABSTRACT: Background. Urinalysis is a poorly reviewed diagnostic tool in malaria patients; its application can show the presence of severe malaria. Methods. Urinalysis was performed in a total of 620 patients diagnosed with malaria by thick blood smear; complications were classified according to WHO major criteria for severity and minor criteria according to the Colombian malaria guideline. Results. Severe or moderate clinical complications were diagnosed in 31.1% of patients, hepatic dysfunctions were diagnosed in 25.8%, anemia was diagnosed in 9.8%, thrombocytopenia was diagnosed in 7.7%, renal dysfunction was diagnosed in 4.8%, neurological and pulmonary complications were diagnosed in 2.1% and 2.4%, hypoglycemia was diagnosed in 1.1% of patients with blood glucose analysis, and acidosis was diagnosed in 10 of 25. Bilirubinuria was found in 24.3%, associated with urobilinuria, proteinuria, and increased specific gravity; urobilinuria was found in 30.6% associated with elevated serum bilirubin and alanine aminotransferase; 39.2% had proteinuria, associated with higher blood urea nitrogen, serum bilirubin, aspartate, alanine-transaminase, hematuria, and increased specific gravity. Severe or moderate liver and renal complications were associated with proteinuria and bilirubinuria. Urobilinuria was associated with thrombocytopenia and neurological and hepatic dysfunction. Ketonuria was associated with neurological dysfunctions. Conclusions. The most frequent alterations in the urinalysis were bilirubinuria, proteinuria, urobilinuria, and increased specific gravity, related to thrombocytopenia and liver, kidney, and neurological alterations.